2019
DOI: 10.1002/chem.201900766
|View full text |Cite
|
Sign up to set email alerts
|

Dyads of G‐Quadruplex Ligands Triggering DNA Damage Response and Tumour Cell Growth Inhibition at Subnanomolar Concentration

Abstract: Naphthalened iimide (NDI) dyads exhibiting ad ifferent substitution pattern and linker length have been synthesiseda nd evaluateda sG -quadruplex (G4) ligands,b yi nvestigating their cytotoxicity in selected cell lines. The dyads with the long C 7 linker exhibit extremelyl ow IC 50 values, below 10 nm,o nd ifferent cancerc ell lines.C ontrary,t he dyads with the shorter C 4 linker were much less effective, with IC valuesi ncreasing up to 1 mm.A mong the three dyads with the longest linker, small differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Finally, to evaluate if the DNA damage induced by NDI-3, NDI-4 and NDI-5 on the transformed cells was located at telomeres, BJ-EHLT cells were treated for 24 h, with each of the three compounds, and the telomeric damage was evaluated by measuring the co-localization spots (telomere-induced foci, TIFs) between γH2AX and TRF1, an effective marker for interphase telomeres ( Figure 5C). Interestingly, quantitative analysis showed that the effects of the three compounds were quite similar, and all of them induced a percentage of TIF positive cells (cells with at least four co-localization spots) and average number of TIFs per cell ( Figure 5D) comparable with the values recently found for other effective NDI dyads [21]. From these data, it is possible to conclude that the selected NDIs are not only potent and effective inducers of telomere localized DNA damage response, but also show a high grade of specificity against transformed cells.…”
Section: Biological Assayssupporting
confidence: 84%
See 4 more Smart Citations
“…Finally, to evaluate if the DNA damage induced by NDI-3, NDI-4 and NDI-5 on the transformed cells was located at telomeres, BJ-EHLT cells were treated for 24 h, with each of the three compounds, and the telomeric damage was evaluated by measuring the co-localization spots (telomere-induced foci, TIFs) between γH2AX and TRF1, an effective marker for interphase telomeres ( Figure 5C). Interestingly, quantitative analysis showed that the effects of the three compounds were quite similar, and all of them induced a percentage of TIF positive cells (cells with at least four co-localization spots) and average number of TIFs per cell ( Figure 5D) comparable with the values recently found for other effective NDI dyads [21]. From these data, it is possible to conclude that the selected NDIs are not only potent and effective inducers of telomere localized DNA damage response, but also show a high grade of specificity against transformed cells.…”
Section: Biological Assayssupporting
confidence: 84%
“…All the final products were characterized by ESI-MS and 1 H-and 13 C-NMR. The characterization data for NDI-1 [29], NDI-3 [21], NDI-15 [29] and NDI-17 [21] were previously reported.…”
Section: Synthesis Of Ndis 1-5 15-17 (Figure 3)mentioning
confidence: 89%
See 3 more Smart Citations